In vitro characterization of [125I]HY-3-24, a selective ligand for the dopamine D3 receptor - Ji Youn Lee; Ho Young Kim; Paul Martorano; Aladdin Riad; Michelle Taylor; Robert R. Luedtke; Robert H. Mach (Frontiers in Neuroscience, 2024)
IntroductionDopamine D3 receptor (D3R) ligands have been studied for the possible treatment of neurological and neuropsychiatric disorders. However, selective D3R radioligands for in vitro binding studies have been challenging to identify due to the high structural similarity between the D2R and D3R. In a prior study, we reported a new conformationally-flexible benzamide scaffold having a high affinity for D3R and excellent selectivity vs. D2R. In the current study, we characterized the in vitro binding properties of a new radioiodinated ligand, [125I]HY-3-24.MethodsIn vitro binding studies were conducted in cell lines expressing D3 receptors, rat striatal homogenates, and rat and non-human primate (NHP) brain tissues to measure regional brain distribution of this radioligand.ResultsHY-3-24 showed high potency at D3R (Ki = 0.67 ± 0.11 nM, IC50 = 1.5 ± 0.58 nM) compared to other D2-like dopamine receptor subtypes (D2R Ki = 86.7 ± 11.9 nM and D4R Ki > 1,000). The Kd (0.34 ± 0.22 nM) and Bmax (38.91 ± 2.39 fmol/mg) values of [125I]HY-3-24 were determined. In vitro binding studies in rat striatal homogenates using selective D2R and D3R antagonists confirmed the D3R selectivity of [125I]HY-3-24. Autoradiography results demonstrated that [125I]HY-3-24 specifically binds to D3Rs in the nucleus accumbens, islands of Calleja, and caudate putamen in rat and NHP brain sections.ConclusionThese results suggest that [125I]HY-3-24 appears to be a novel radioligand that exhibits high affinity binding at D3R, with low binding to other D2-like dopamine receptors. It is anticipated that [125I]HY-3-24 can be used as the specific D3R radioligand.